Worsening of esophageal dilatation is associated with increase in a high-resolution computed tomography (HRCT) score in early systemic sclerosis-associated interstitial lung disease (SSc-ILD) - Suparaporn Wangkaew (2020)
© 2020, International League of Associations for Rheumatology (ILAR). Background: Data regarding longitudinal association between changes (Δ: time2-time1) in the widest esophageal diameter (WED) and Δ HRCT score in early SSc-ILD patients is limited. We therefore investigated the association of ΔWED with Δ HRCT score and predictors of a worse Δ HRCT score in those patients. Methods: We used an inception cohort of early SSc-ILD patients with availability for two HRCT records at enrollment and 1-year follow-up.The extent of ground glass, reticulation, bronchiectasis, and honeycombing was scored and then aggregated to produce a total HRCT score. The WED was measured at four levels and the maximum value was used. The Δ maximum WED, Δ mean WED, and Δ tHRCT score were analyzed. Results: We recruited 75 early SSc-ILD patients and found a significant correlation of Δ tHRCT score with a Δ maximum WED (rho = 0.34, p < 0.01) and Δ mean WED (rho = 0.26, p < 0.05). There were 34 patients with a worsening Δ tHRCT (Δ > 0), 17 with stability (Δ = 0), and 24 with improvement (Δ < 0). Patients with a worsening ILD had a significantly shorter disease duration, lower prevalence of tendon friction rub, higher cumulative prednisolone dose, and larger ΔWED than those with stable and improved Δ tHRCT scores. Multivariate ordinal logistic regression identified a larger Δ mean WED (OR 1.21, 95% CI 1.03–1.42, p = 0.02) as a predictor of worsening HRCT score, while presence of tendon friction rub was associated with a lower risk (OR 0.18, 95% CI 0.04–0.77, p = 0.021). Conclusion: Our study cohort found that a worsening esophageal diameter was a predictor of progression of lung fibrosis determined by HRCT score in early SSc-ILD. A further study regarding esophageal dilation progression different in early versus longstanding SSc-ILD is needed.Key Points•In early SSc-ILD patients, we demonstrated that a worsening esophageal diameter was a predictor of progression of HRCT score at 1-year follow-up.•Further study regarding the association of worsening of the esophageal dilatation with the progression of ILD comparing between early versus late SSc-ILD is needed.